Construing God: An Exploration of the Relationships between Reported Interaction with God and Concurrent Emotional Experience - Preston, Carol A. (Journal of psychology and theology, 1986)
This study explores the subjective experience of individuals as they intract with God It is proposed that through the model of personal construct psychology insights can be gained into people's perceptions of God, the roles God plays in their lives, and the affective implications of such interactions. Subjective experience was assessed using content analysis of verbalizations from 150 people identifying themselves as Christians. Four kinds of interactions with God were considered, involving different constructions of God. Different affective experience was found to be related to the interactions. The implications of these relationships are discussed The data provide insights into the meaning of relating to God as part of human experience.